Myocardial deformation in pediatric patients with mucopolysaccharidoses: A two‐dimensional speckle tracking echocardiography study. Issue 2 (10th January 2017) - Borgia, Francesco; Pezzullo, Enrica; Schiano Lomoriello, Vincenzo; Sorrentino, Regina; Lo Iudice, Francesco; Cocozza, Sara; Della Casa, Roberto; Parenti, Giancarlo; Strisciuglio, Pietro; Trimarco, Bruno; Galderisi, Maurizio
Abstract : Background: Mucopolysaccharidoses (MPS) are inherited lysosomal storage disorders caused by deficiency of required glycosaminoglycans breakdown enzymes, inducing cardiac involvement. Little is known about myocardial deformation involvement in MPS. Our aim was to assess biventricular structure and function in asymptomatic children with MPS using standard echo Doppler and 2D speckle tracking (STE). Methods: Fifteen MPS children (one type I, six type II, three type III A, one III B, three IV A, one VI), asymptomatic for cardiac symptoms, and 15 age and sex‐matched healthy controls underwent echo Doppler and STE. Left ventricular (LV) wall thicknesses, diameters, and mass were normalized by z ‐score. LV global longitudinal strain (GLS), global circumferential strain (GCS), global radial strain (GRS) at papillary muscles, LV twisting, and right ventricular (RV) GLS were measured. Results: The two groups were comparable for body mass index, heart rate, and blood pressure. LV mass index and relative wall thickness were higher in MPS. Ejection fraction (EF), and s′ velocity did not differ between the two groups. E/A ratio was lower and E/e′ higher in MPS. Tricuspid annular plane systolic excursion, RV s′ and e′ were lower in MPS. LV GLS did not differ between the two groups, but GCS ( P =.014), GRS ( P =.023), twisting ( P =.012), and RV GLS ( P <.001) were lower in the MPS group. Conclusions: LV strain abnormalities are detectable in MPS pediatric patients, independently of MPS type, when EF is still normal. RV GLS is also involved consensually with TAPSE reduction. STE can be useful for detection of subclinical myocardial damage in MPS.